A phase 1 dose‐escalation study of the poly(ADP‐ribose) polymerase inhibitor senaparib in Australian patients with advanced solid tumors. Issue 7 (31st January 2023) - Gao, Bo; Voskoboynik, Mark; Cooper, Adam; Wilkinson, Kate; Hoon, Siao; Hsieh, Chih‐Yi; Cai, Suixiong; Tian, Ye Edward; Bao, Jun; Ma, Ning; Wang, Chen; Zhang, Ming; et al.
Abstract: Background: Senaparib is a novel, selective poly(ADP‐ribose) polymerase‐1/2 inhibitor with strong antitumor activity in preclinical studies. This first‐in‐human, phase 1, dose‐escalation study examined the safety and preliminary efficacy of senaparib in patients with advanced solid tumors. Methods: Patients with advanced solid tumors were enrolled from three centers in Australia, using a conventional 3 + 3 design. Dose‐escalation cohorts continued until the maximum tolerated dose or a recommended phase 2 dose was determined. Patients received one dose of oral senaparib and, if no dose‐limiting toxicity occurred within 7 days, they received senaparib once daily in 3‐week cycles. The primary end points were safety and tolerability. Results: Thirty‐nine patients were enrolled at 10 dose levels ranging from 2 to 150 mg. No dose‐limiting toxicities were observed in any cohort. Most treatment‐emergent adverse events were grade 1–2 (91%). Seven patients (17.9%) reported hematologic treatment‐emergent adverse events. Treatment‐related adverse events occurred in eight patients (20.5%), and the most frequent was nausea (7.7%). Two deaths were reported after the end of study treatment, one of which was considered a complication from senaparib‐related bone marrow failure. Pharmacokinetic analysis indicated that senaparib the accumulation index was 1.06–1.67, and absorption saturation was 80–150 mg daily. In 22 patients with evaluable disease, the overall response rate was 13.6%, and the disease control rate was 81.8%. The overall response rate was 33.3% for the BRCA mutation‐positive subgroup and 6.3% for the nonmutated subgroup. Conclusions: Senaparib was well tolerated in Australian patients with advanced solid tumors, with encouraging signals of antitumor activity. The recommended phase 2 dose for senaparib was determined to be 100 mg daily. ClinicalTrials.gov ID: NCT03507543. Abstract : The novel, oral poly(ADP‐ribose) polymerase‐1/2 inhibitor senaparib was safe and well tolerated, with encouraging signals of antitumor activity, in patients in Australia with relapsed or refractory advanced solid tumors. A comprehensive analysis of safety, pharmacokinetic, and efficacy findings confirmed that the recommended phase 2 dose of senaparib in Australian patients should be 100 mg once daily.